(untitled) (Journal of the Entomological Research Society, 2025)
A study, conducted during the litchi blooming period of 2022 and 2023, provided valuable insights into the diversity and foraging behaviour of bee visitors associated with litchi flowering in the sub-Himalayan Terai region of West Bengal. The study enlisted 15 species of bees from 5 families, namely Andrenidae (1 species), Apidae (7), Colletidae (1), Halictidae (4), and Megachilidae (2), visiting the litchi bloom. Among them, Apidae family alone contributed 49.56% of the total bee assemblage. As an individual species, Apis mellifera was the most frequent visitor (1.09 individuals/m2/minute). In contrast, Megachile laticeps was the least abundant (0.28 individuals/m2/minute) visitor with least foraging speed (2.20 seconds) and highest foraging rate (13.96 flowers/minute/forager). A good diversity of bees was ensured by the higher values of Shannon diversity (2.672) and Margalef richness (2.385) indices. Furthermore, higher value of Sheldon evenness (0.965) and lower value of Simpson dominance (0.071) indices confirmed no prominent dominance of a single/few species in the assemblage. Weather parameters like Tmax, RHmin, BSH, and wind speed had significant (p<0.05) effects on the foraging parameters. Maximum foraging activity of different bee visitors was recorded at 10:00-12:30 hours. Thus, by understanding these dynamics, it may be possible to develop targeted strategies to conserve and support these vital pollinators and ensure sustainable litchi production in the region.